Hyaluronic acid/chitosan-coated poly (lactic-co-glycolic acid) nanoparticles to deliver single and co-loaded paclitaxel and temozolomide for CD44+oral cancer cells - Mesrati, Malak Hassn; Ahmad Tajudin, Asilah; Masarudin, Mas Jaffri; Alamassi, Mohammed Numan; Abuhamad, Asma Y.; Syahir, Amir (Elsevier BV, 2023)
Oral cancer has a poor survival rate despite comprehensive therapy. Current treatments result in acute side effects and fail to eliminate an aggressive group of cells overexpressing CD44. Such cells are capable of tumour initiating, self-renewal, invasion and metastasis, resulting in tumour relapse and resistance. This study aims to synthesise and characterise hyaluronic acid/chitosan-coated poly (lactic-co-glycolic acid) nanoparticles and assess their effectiveness in delivering Paclitaxel and Temozolomide to human tongue squamous cell carcinoma cell line that expresses high CD44 levels, in terms of cell cytotoxicity and apoptosis. This study also assesses the coordinated administration of Paclitaxel and Temozolomide and whether they exhibit significant synergistic cell inhibition effects with reduced introduced drug concentration if co-delivered simultaneously. Nanoparticles were synthesised with solvent evaporation method and characterised to assess their size, homogeneity, and zeta potential. Cell viability assay and real-time cell analysis were performed to examine the cell inhibitory effect of the drug-loaded nanoparticles. Cell apoptosis and cell cycle alteration were detected, and reactive oxygen species induction, mitochondrial membrane potential, and expressed genes associated with cell inhibition and death were evaluated. The synthesised nanoparticles had a nano-sized diameter of 260.40±11.54 nm, a positive zeta potential of +14.31±1.37 mV and a low polydispersity index value of 0.15±0.03. Paclitaxel, Temozolomide, and their combination have inhibited cell proliferation with half maximal inhibitory concentrations of 4 nM, 1000 μM and 2nM:300 μM, respectively. Compared to free drugs, the single-loaded and co-loaded drugs induced more cytotoxicity. Paclitaxel and Temozolomide showed a considerable synergistic inhibitory effect which was discovered to be more significant when the drugs were loaded in the nanoparticles. Drug-loaded nanoparticles were verified to induce higher cell apoptosis rates, cell proportion arrested at the S-phase of the cell cycle, reactive oxygen species generation, mitochondrial collapse and expression of genes associated with cellular inhibition and death than free drugs. These results demonstrate that the established nanoparticles could be a potential candidate for oral cancer therapy since they could deliver and improve the efficacy of single and dual drugs against oral cancer cells.